Functional analysis of mRNA methylation in plants - Zhang, Mi (2018)
RNA modifications, which collectively constitute the epitranscriptome, have been found to play a crucial role in regulating gene expression. N6-methyladenosine (m6A) is a ubiquitous base modification in mRNAs of most eukaryotes and is implicated in multiple biological processes. The formation of m6A is catalysed by the methyltransferase (MTase) complex (m6A writer complex), composing of MTA, MTB, FIP37, Virilizer and Hakai (an E3 ubiquitin ligase). As a novel member of the MTase complex, the role of Hakai in mRNA methylation both in plants and in mammals is not yet understood. In addition, the biological functions of m6A in plants is far from well characterised. The aim of this study is to elucidate the function of Hakai, interactions between different components of the MTase complex and the regulatory role of m6A in root development. Based on characterising mutants and transgenic lines generated via CRISPR-Cas9, crossing and floral dip transformation in combination with m6A measurements, confocal microscopy, transcriptional and protein level analysis, proteomic assay, etc., the following results and conclusions are reached. The knockout of Hakai led to approximately 40% decrease of m6A level and this could be restored by complementation with a wild-type Hakai transgene. MTA, FIP37 and Virilizer among known m6A writer proteins were interacting partners of Hakai. mta hakai double mutants demonstrated more severe developmental defects while hakai fip37 and hakai virilizer appear to be lethal. Therefore, Hakai is an important m6A writer protein, acting synergistically with other m6A writer proteins to properly perform m6A modification and regulate plant growth and development. In addition, novel proteins interacting with both MTA and Hakai were identified, including two zinc-finger proteins (AT1G32360 and AT5G53440) and Hakai is required for the interaction between MTA and AT1G32360. All low m6A mutants demonstrated strong auxin-insensitive phenotypes: dramatically shorter primary roots and reduced lateral roots relative to WT, indicating m6A might have a regulatory role in mediating the auxin signalling network. Strikingly, auxin response factor 7 (ARF7) protein level increased upon the knockout of FIP37 or Virilizer while its mRNA level and ARF8 protein level were unchanged. Given that ARF7 contains upstream open reading frames (uORFs) but this is not the case for ARF8, we propose that m6A might be responsible for translational regulation of some uORF-containing transcripts. Collectively, the data in this study shed new light on interactions between m6A writer proteins and regulatory mechanisms of m6A modification, which will aid our understanding of the function of eukaryotic mRNA methylation.